Platelet function is modified by common sequence variation in megakaryocyte super enhancers - Romina Petersen; John J. Lambourne; Biola M. Javierre; Luigi Grassi; Roman Kreuzhuber; Dace Ruklisa; Isabel M. Rosa; Ana R. Tomé; Heather Elding; Johanna P. van Geffen; Tao Jiang; Samantha Farrow; et al. (Nature Communications, 2017)
Numerous genetic variants, including those located in the non-coding regions of the genome, are known to be associated with blood cells traits. Here, Frontini and colleagues investigate their potential regulatory functions using epigenomic data and promoter long-range interactions.